2018
DOI: 10.1186/s12984-018-0450-3
|View full text |Cite
|
Sign up to set email alerts
|

Manual wheelchair downhill stability: an analysis of factors affecting tip probability

Abstract: BackgroundFor people who use manual wheelchairs, tips and falls can result in serious injuries including bone fractures, concussions, and traumatic brain injury. We aimed to characterize how wheelchair configuration changes (including on-the-fly adjustments), user variables, and usage conditions affected dynamic tip probability while rolling down a slope and contacting a small block.MethodsRigid body dynamic models of a manual wheelchair and test dummy were created using multi-body software (Madymo, TASS Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Another interesting finding was that males did not report any falls while wheeling over uneven ground. According to previous literature, the weight of a wheelchair user can impact the wheelchair's stability and maneuverability [58]. One possible explanation for our finding is that males tend to weigh more than females [59] and due to heavier weight, males may be less likely to tip while going over uneven ground in a manual wheelchair.…”
Section: Plos Onementioning
confidence: 61%
“…Another interesting finding was that males did not report any falls while wheeling over uneven ground. According to previous literature, the weight of a wheelchair user can impact the wheelchair's stability and maneuverability [58]. One possible explanation for our finding is that males tend to weigh more than females [59] and due to heavier weight, males may be less likely to tip while going over uneven ground in a manual wheelchair.…”
Section: Plos Onementioning
confidence: 61%
“…The performance of manual wheelchair players is also related to the wheelchair user position relative to the main axle position (Brubaker, 1986). Thomas et al (2018) indicated that reclining the wheelchair seat relative to the horizontal axis increased stability in a wheelchair user. According to Haydon et al (2016), the seat angle of the DW used by LP players was significantly higher than the seat angle of the OW used by HP players.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of wheelchair type and configuration has been studied from different points of views: weight, configuration or typical usage [12,13,14,15,16,17,18]. The objective, in all cases, is to unveil the relationship between these factors and the risk of lesions on the patients.…”
Section: Introductionmentioning
confidence: 99%